Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/10454446.2020.1782796
|View full text |Cite
|
Sign up to set email alerts
|

Determining How Chinese Consumers that Purchase Western Food Products Prioritize Food Safety Cues: A Conjoint Study on Adult Milk Powder

Abstract: This study investigated how Chinese consumers prioritize cues when assessing the safety of imported milk powder. A choice-based conjoint survey was completed by 307 participants in Beijing, Shanghai, Tianjin, and Nanjing, using the internet-based software 1000minds. Important cues for consumers were "government certification logo shown on the product label/Website"; "ingredients and materials, free from preservatives and additives"; "having traceability techniques such as QR code included" and "realistic photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Chinese manufacturers tended to provide information on farm details, production standard, traceability as well as the corresponding certificates, but such food safety related VWM was seldom mentioned on international products. Recently, it was reported that due to the heightened awareness of food safety in China, Chinese consumers expect to see food safety-related information not only on domestic, but also imported milk powders [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chinese manufacturers tended to provide information on farm details, production standard, traceability as well as the corresponding certificates, but such food safety related VWM was seldom mentioned on international products. Recently, it was reported that due to the heightened awareness of food safety in China, Chinese consumers expect to see food safety-related information not only on domestic, but also imported milk powders [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twentythree participants found these five attributes to be crucial to their wine selection. The 1000minds software (Hansen and Ombler, 2008), which adapts PAPRIKA (Potentially All Pairwise RanKings of all possible Alternatives) method, is a full factorial DCE that is widely used in research (Baggott et al, 2019;Mirosa et al, 2020) and was used to collect the data from the respondents. Also known as conjoint analysis (McFadden, 1974), it is an extensively used technique to find consumers' choices involving trade-offs between alternative product attributes of interest.…”
Section: Methodsmentioning
confidence: 99%
“…com), which implements the PAPRIKA method -an acronym for Potentially All Pairwise RanKings of all possible Alternatives (Hansen and Ombler, 2008). The software and method have been used in a wide range of business-related areas; recent examples include measuring businesses' reputations (Whiting et al, 2017), transport infrastructure planning (Miller and Gransberg, 2017), marketing research (Mirosa et al, 2020;Parsad et al, 2019) and for understanding wellness tourism in Japan (Romão et al, 2018).…”
Section: Methodsmentioning
confidence: 99%